(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The approach proposed in this study aims to highlight the problem when double taxation occurs in the PIS and COFINS taxes when the taxable person is the microenterprises and small companies that opt ​​for the SIMPLES single collection system. It should be noted that the double tax incidence is vetoed by our legal system, analyzing that the occurrence of this fact must be by the debelado State. Keywords: Zero rate; Tax Incidence; SIMPLE; PIS; COFINS.